2009
DOI: 10.1097/aud.0b013e31819f3145
|View full text |Cite
|
Sign up to set email alerts
|

Infant Air and Bone Conduction Tone Burst Auditory Brain Stem Responses for Classification of Hearing Loss and the Relationship to Behavioral Thresholds

Abstract: AC- and BC-TBABR results can be readily obtained in young infants under natural sleep and were used to classify the type of HL based on the absolute threshold and the size of the ABG. Differences in wave V latency functions for TBABR by AC and BC and wave I and V latencies of the high-level click ABR also distinguish between infants with and without TBABR ABGs. Ear-specific behavioral responses can be obtained at levels under 20 dB HL in normal-hearing infants younger than 1 yr using VRA, and these behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
64
1
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 46 publications
16
64
1
13
Order By: Relevance
“…This finding corroborate several studies 14,[16][17][18][19][20] , in which the mean MRL were different from the present study by less than 10 dB. A meta-analysis and a study conducted in 2007 both showed lower MRL -19.6 and 18.4 dBnHL, respectively 11,21 .…”
Section: Presence Of Wave Vsupporting
confidence: 81%
See 3 more Smart Citations
“…This finding corroborate several studies 14,[16][17][18][19][20] , in which the mean MRL were different from the present study by less than 10 dB. A meta-analysis and a study conducted in 2007 both showed lower MRL -19.6 and 18.4 dBnHL, respectively 11,21 .…”
Section: Presence Of Wave Vsupporting
confidence: 81%
“…At the intensity of 30 dBnHL, some studies have found mean latencies similar to those in the present study 18,20,35 . In the frequency of 1000 Hz, at 80 dBnHL, the latency time was 8.61±0.38 ms, shorter than the results of another study conducted in Brazil frequency suggest responses at intensities lower than 20 dBnHL 10,14,[19][20][21][22] . However, in the present research, the newborns were in natural sleep and not sedated, as in some o these previous studies, which justified the option for the minimum intensity level of 20 dBnHL, as previously described in the methods.…”
Section: Function Latency X Intensitycontrasting
confidence: 38%
See 2 more Smart Citations
“…A minimum of two recordings per intensity were used to determine wave reproducibility, and provide more test reliability. diagnosis, primarily in characterizing hearing loss 4,6,28,34 .…”
Section: Study 31mentioning
confidence: 99%